CEO Tenure, Market Competition, and Sticky Pay‐without‐performance as the Extraction of Rents. (29th April 2017) - Kim, Jinbae; Yang, Daecheon; Lee, Minyoung
Abstract: This study examines the undesirable impact of CEO tenure on downwardly sticky pay, and the moderating effect of higher market competition on the potential adhesive connection between CEO tenure and sticky pay. We find that CEO pay stickiness intensifies as CEO tenure increases. This suggests that entrenched executives extract greater levels of baseline rents through strong exclusivity. In contrast, we find that in firms with long‐tenured CEOs, higher levels of competition intensity alleviate CEO pay stickiness. These results imply that although long‐tenured CEOs tend to exert a powerful influence over the pay‐setting process, increased competition restrains CEOs' rent‐seeking behavior.